Annual Survey of Jails in Indian Country, 2000: (United States) ([Verlag nicht ermittelbar], 2001)
The objective of the Survey of Jails in Indian Country is to gather data on all adult and juvenile jail facilities and detention centers in Indian country, which is defined for purposes of this collection as reservations, pueblos, rancherias, and other Native American and Alaska Native communities throughout the United States. The survey, a complete enumeration of all 69 confinement facilities operated by tribal authorities or the Bureau of Indian Affairs (BIA), provides data on the number of inmates and facility characteristics and needs. Variables describe each facility, including the rated capacity, number of adult inmates, number of juveniles held, number of inmates held by sex and conviction status on June 30, number of admissions and discharges in the last 30 days, number of inmate deaths, peak population during June, facility crowding, and renovation and building plans.